Large field-of-view nanometer-sectioning microscopy by using metal-induced energy transfer and biexponential lifetime analysis - Wonsang Hwang (Nature Portfolio, 2021)
Hwang et al. demonstrate that a high axial resolution can be achieved even with low numerical aperture (NA) objectives. They show the nano-profile of a basal cell membrane using metal-induced energy transfer and biexponential fluorescence lifetime analysis. The low-NA objective provides a larger field-of-view (FOV), thereby overcoming the limitations of a small FOV of the usually used high-NA objectives.